Gender violence: conceptual difference in European and Latin American legal systems - Rivas Vallejo, Pilar (2020)
Gender violence is a concept coined and consolidated by the various international legal instruments of the United Nations, the Council of Europe and the Parliament of the European Union, as well as the Inter-American and Pan-American conventions, among others, conceptualizing it as gender discrimination and as serious violation of human rights. In Latin America, the legal figure of femicide makes visible the seriousness of the problem, and some legislations have opted for an expansive concept of gender violence in their comprehensive protection laws, while in the European sphere only violence in the context of a sentimental relationship is subject to specific treatment.